Intervening aspects on the influence of Strategic Environmental Assessment on the development of Plans and Programs in Brazil - Tshibangu, Ghislain Mwamba (2019)
Strategic Environmental Assessment (SEA) is an impact assessment tool that can facilitate sustainable development and improve decision-making by introducing environmental concern early in planning processes. In recent years, there has been a rising interest in studies on the effectiveness of SEA, which is measured by comparing the instrument outcomes and theoretical, procedural and objective aspects of its performance. This confrontation highlights the tool influence on decisions taken and, above all, its actual effects on the environment. Literature on SEA indicates that there is a need to identify evidence regarding impacts of SEA on the process of formulating and implementing strategic actions, especially in order to highlight its real benefits and its contribution to the society. Based on these considerations, the PhD thesis aims to explore the extent to which the context may influence on SEA effectiveness based on perceived SEA outcomes. Considering characteristics of the SEA system in Brazil, the methodology used in this study involved the following steps: (i) identification of actors and institutions involved in the SEA processes, and (ii) identification of SEA outcome(s) through questionnaire and interview survey. The second step involved previously a systematic analysis of literature focusing on SEA outcomes and impacts on decision-making. A total of 68 SEAs applied in Brazil from 1997 to 2018 was identified. The findings indicate three main aspects that may explain the lengthy process of introduction of SEA in plan- and policy-making in the country: (i) lack of proper SEA legislation; (ii) the influence of Environmental Impact Assessment practice, and; (iii) the strong influence of the environmental licensing culture. Nevertheless, SEA contribute to improving communication between stakeholders along the planning process and to providing a better level of information for lower tiers of decision-making. In spite of the minor influences on the nature of the strategic action, as reported by interviewees, valuable lessons credited to SEA have been learnt.